Triatomines in the city: A study of Rhodnius neglectus in Jaboticabal, São Paulo, Brazil, and its epidemiological implications - Belintani, Tiago [UNESP]; de Oliveira, Jader; de Paiva, Vinícius Fernandes [UNESP]; Santana, Jociel Klleyton Santos [UNESP]; Fernandes, Isabella Maxwell Paulino [UNESP]; Gomes, Jonathan Silvestre [UNESP]; Hoppe, Estevam Guilherme Lux [UNESP]; da Rosa, João Aristeu [UNESP] (FapUNIFESP (SciELO), 2024)
Background: Chagas disease, a significant global health concern rooted in social inequalities and political oversights, remains a challenging public health issue impacting millions worldwide. The increasing detection of triatomines, the vectors of Chagas disease, in urban areas complicates the situation. Methods: This study investigated the incidence of Rhodnius neglectus in the urban areas of Jaboticabal, São Paulo, Brazil, following several reports and previous collections of triatomines in the city. An educational approach was adopted, distributing informational materials and engaging the community through social networks to generate notifications that would enable the identification of triatomines. Specimens were collected using various methods, including passive surveillance actions, light traps, and active searches in palm trees. Results: Rhodnius neglectus was found in urban areas, invading homes in Jaboticabal, and was identified in palm trees. The educational approach led to the collection of 93 triatomines. Colonization was observed in a residence, with eggs, nymphs, and a concerning record of blood-feeding on a resident child. The houses where specimens were captured often had nearby palm trees with birds and nests, facilitating the passive transport of these insects and increasing the risk of invasion due to light attraction. No triatomines infected with Trypanosoma cruzi were identified. Conclusions: These findings emphasize the need for preventive measures to reduce the prevalence of R. neglectus in urban environments. The data elucidate the occurrence of R. neglectus in the city of Jaboticabal, associated with its potential behavioral adaptation in urban environments, underscoring the need for innovative control strategies.
Keywords: Chagas disease; Triatominae; Urban vectors; Urbanization; Vector control